SISTEM EKONOMI ISLAM DENGAN ASPEK KEHIDUPAN MASYARAKAT MADANI DITINJAU DARI HUKUM ISLAM - Dwika Mayasari; Sarah Wijayanti Putri (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2020)
The system of Islamic economics is supporting in realizing the economy of Madani society (civil society). The failure of the conventional system causes social values and morals to deviate from society so that the system is considered a failure in shaping the community's economy. For this reason, the shari'ah economy is an alternative in the formation of the economy in Madani society through instruments such as bait al-maal, zakat institutions, waqf institutions, alms, and others.